Human-specific CpG 'beacons' identify human-specific prefrontal cortex H3K4me3 chromatin peaks. (February 2014) - Bell, Christopher G; Wilson, Gareth A; Beck, Stephan
Background : Targeted recruitment of chromatin-modifying enzymes to clusters of CpG dinucleotides contributes toward the formation of accessible chromatin. By interprimate comparison we previously identified the set of nonpolymorphic human-specific CpGs (CpG 'beacons') and revealed that these loci were enriched for human disease traits. Due to their human-specific CpG density change, extreme CpG 'beacon' clusters (≥20 CpG beacons/kb) were predicted to identify permissive chromatin peaks within the human genome.Aim: We set out to explore these sequence-defined regions for evidence of an active chromatin signature.Results : Using available comparative primate epigenomic data from neurons of the prefrontal cortex, we show that these CpG 'beacon' clusters are indeed enriched for being human-specific H3K4me3 peaks (χ 2 : p < 2.2 × 10 −16 ) and thus predictive of permissive chromatin states. These sequence regions had a higher predictive value than previous selective analyses. We also show that both human-specific H3K4me3 and CpG 'beacon' clusters are increased within current and ancestral telomeric regions, supporting an association with recombination, which is higher towards the distal ends of chromosomes.Conclusion : Therefore, CpG-focused comparative sequence analysis can precisely pinpoint chromatin structures that contribute to the human-specific phenotype and further supports an integrated approach in genomic and epigenomic studies.